2016
DOI: 10.1007/s11356-016-7704-z
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of bio-oil from the pyrolysis of waste frying oil

Abstract: In this present work, the disposal of waste frying oil was explored. The experiment tests were performed under nitrogen (N) atmosphere at 5 °C/min heating rate from the ambient temperature to 500 °C. In these operating conditions, the obtained pyrolitic liquid fraction was 76 wt% formed by 63.87 wt% of crude bio-oil and 12.13 wt% of aqueous fraction. The chemical characterization using FTIR, GC, and GC/MS has revealed that the bio-oil is a complex chemical mixture of linear saturated, unsaturated, and cyclic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 37 publications
6
25
0
Order By: Relevance
“…Generally, triglyceride pyrolysis mechanisms are difficult due to their complex chemical structures [42]. Figure 8 [42] shows the decomposition of a triglyceride reaction. Bio-oil obtained from the thermal pyrolysis of sunflower oil is a complex mixture of organic compounds with carbon atom number from C15 to C37 (n-alkanes e branched alkenes) and oxygenated products such as aldehydes, ketones, carboxylic acids, alcohols and esters.…”
Section: Catalytic Testmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, triglyceride pyrolysis mechanisms are difficult due to their complex chemical structures [42]. Figure 8 [42] shows the decomposition of a triglyceride reaction. Bio-oil obtained from the thermal pyrolysis of sunflower oil is a complex mixture of organic compounds with carbon atom number from C15 to C37 (n-alkanes e branched alkenes) and oxygenated products such as aldehydes, ketones, carboxylic acids, alcohols and esters.…”
Section: Catalytic Testmentioning
confidence: 99%
“…As the pyrolysis temperature used in this study is low (500 • C), the formation of carbon dioxide, carbon monoxide and aromatic, aliphatic and cyclic hydrocarbons was not observed. Generally, triglyceride pyrolysis mechanisms are difficult due to their complex chemical structures [42]. Figure 8 [42] shows the decomposition of a triglyceride reaction.…”
Section: Catalytic Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the adsorption kinetics was strongly improved in the presence of AC. Kraiem et al (2017) have explored the disposal of waste frying oil. Pyrolysis was used to treat the liquid waste in order to improve the quality of the produced bio-oil.…”
mentioning
confidence: 99%